British Association of Dermatologists guidelines for biologic therapy for psoriasis 2020: a rapid update. (1st October 2020) - Smith, C.H.; Yiu, Z.Z.N.; Bale, T.; Burden, A.D.; Coates, L.C.; Edwards, W.; MacMahon, E.; Mahil, S.K.; McGuire, A.; Murphy, R.; Nelson‐Piercy, C.; Owen, C.M.; et al.
Abstract: Linked Comment: Ormerod. Br J Dermatol 2020; 183 :604 . Plain language summary available online